Peran Perempuan dalam Pembangunan Desa - Handrianus Vianey Melin Wula; Tri Anggraini (Kaganga:Jurnal Pendidikan Sejarah dan Riset Sosial Humaniora, 2022)
This study aims to find out the roles and barriers of women in their contribution to village development in Subun Bestobe Village, Insana Barat District, North Central Timor Regency. The research method uses qualitative methods. The results showed that the role of women in village development in Subun Bestobe Village is the role in self-help groups and the size of women's participation is in various fields, namely; politics, customs, government, education, health and welfare. The conclusion of this study is that the involvement and level of women's participation in village development is good, but in terms of quantity, the number of village officials is very minimal. There is equality and partnership in every existing process to build dialogue without taking into account the gender and structure of each party in village development efforts. All parties have been able to develop communication and an open and conducive communication climate so as to create dialogue in the village development process. In village development, the various parties involved can balance the distribution of authority and power to avoid certain gender domination. Keywords: The Role of Women, Village Development.